THE MANGROVE FORESTS OF CAIRNS, NORTHERN AUSTRALIA - Hegerl, E. J.; Davie, J. D.S. (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 1977)
Surveys of the flora and fauna of the Cairns tidal wetlands were carried out by members of the Australian Littoral Society during the summers of 1974 and 1975. These wetlands cover an area of 6000 hectares in Trinity Inlet and the Barron River delta. The Cairns mangrove and saltmarsh vegetation forms distinct patterns of zonation which appear to be largely controlled by the volume and constancy of freshwater flow. The results of extensive collections revealed a wetlands associated fauna of invertebrates and fish that is considerably more diverse than has previously been reported for northern Queensland. While some species are ubiquitous, many of the invertebrates have been found only in a discrete habitat within particular zones of vegetation. Species diversity of molluscs and crustaceans is greatest in the most constantly inundated zones. A diverse fauna occurs in rotted mangrove logs. Data were obtained on the export of organic material from a small mangrove watershed on one day in December 1975. These revealed a figure for detritus of 11.3 gC/m2/day. This was composed of a 'dissolved' organic carbon fraction of 6.3 gC/m2/day, and 5.0 gC/m2/day of particulate organic carbon. These figures are discussed in relation to available literature on mangrove forests and estuaries. Rapid urban and agricultural development of Cairns is now placing a large portion of these wetlands under serious threat of destruction. The prospects for the future conservation of the Cairns tidal wetlands are discussed.